Concordance of risk behavior reporting within HCV serodiscordant injecting partnerships of young injection drug users in San Francisco, CA - Evans, Jennifer L. (Drug Alcohol Depend, 2014)
INTRODUCTION: Young injection drug users (IDU, under age 30) often inject with other IDU, creating an environment for risk of blood-borne disease transmission through sharing of needles and drug preparation equipment. Epidemiologic studies rely on self reported injection behavior data for measures of transmission risk, therefore we sought to quantify the degree of concordance of reported injecting risk behaviors between injecting dyads. METHODS: From May, 2006 through 2013 we enrolled 72 injecting dyads in San Francisco, California, who were hepatitis C virus (HCV) RNA discordant. Each partnership was followed prospectively for up to six months. Monthly interviews from each partner were date-matched and responses to relationship characteristics and risk behavior questions were compared. Concordance of reporting was estimated with the concordance correlation coefficient for longitudinal data (CCC) and the prevalence adjusted bias adjusted kappa (PABAK). RESULTS: Participants had a median age of 26 (IQR: 23, 28) years and median years injecting of 7.0 (IQR: 3.0,10.6). Thirty-eight percent of the injecting dyads were also sexual partners. Concordance levels were highest for partnership characteristics, such as length of acquaintance, number of days cohabitating, and sexual intercourse in the past month (CCC = 0.95; 0.82, and 0.90, respectively). Shared injection risk behaviors such as injecting with the HCV+ partner’s previously used syringe and using contaminated injection preparation equipment had slight to fair agreement (CCC = 0.22; 0.23; PABAK = 0.43,0.36, respectively). CONCLUSIONS: Concordance levels ranged from low to high. Potential sources of measurement error for low agreement items include recall and social-desirability biases and question interpretation.